2016
DOI: 10.1016/j.jval.2016.09.1121
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Once-Yearly Injection of Zoledronic Acid For The Treatment of Osteoporosis In Japan

Abstract: Summary Model-based economic evaluation was performed to assess the cost-effectiveness of zoledronic acid. Although zoledronic acid was dominated by alendronate, the incremental quality-adjusted life year (QALY) was quite small in extent. Considering the advantage of once-yearly injection of zoledronic acid in persistence, zoledronic acid might be a cost-effective treatment option compared to once-weekly oral alendronate. Introduction The purpose of this study was to estimate the cost-effectiveness of once-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…This finding is similar to the study of Parthan et al [21] and Yoshizawa et al [29]. In addition, Moriwaki et al [30] reported that the relative risk of hip fracture with zoledronic acid had a relatively strong effect on the estimated incremental net monetary benefit; compared to alendronate, zoledronic acid could be a cost-effective option if the relative risk was equal to 0.34 (lower limit).…”
Section: Drug Effect On the Risk Of Fracturessupporting
confidence: 87%
See 3 more Smart Citations
“…This finding is similar to the study of Parthan et al [21] and Yoshizawa et al [29]. In addition, Moriwaki et al [30] reported that the relative risk of hip fracture with zoledronic acid had a relatively strong effect on the estimated incremental net monetary benefit; compared to alendronate, zoledronic acid could be a cost-effective option if the relative risk was equal to 0.34 (lower limit).…”
Section: Drug Effect On the Risk Of Fracturessupporting
confidence: 87%
“…Oral bisphosphonates were included in 11 studies [13-15, 18, 21, 22, 24-26, 29, 30] and compared with other active interventions. There were three studies [16,20,28] considering sequential therapies as comparators, while six studies [15,17,[30][31][32]36] made the comparison between active osteoporotic drugs and calcium/ vitamin D 3 and ten studies [12, 18, 19, 23-25, 27-29, 33, 34] included no treatment as the comparator. Treatment duration in most studies was similar to randomized controlled trials, indications, or guidelines (e.g., 3 or 5 years for anti-resoptive agents, 12-24 months for anabolic agents).…”
Section: Idenɵficaɵonmentioning
confidence: 99%
See 2 more Smart Citations
“…Health economic evaluation studies in osteoporosis are few in the Asia-Pacific region. Robust studies have been conducted in a few countries including Singapore [95], China [96,97], Japan [98,99], and Australia [100]. These studies have employed different modeling strategies and have explored cost-effectiveness of fracture intervention thresholds as well as of various osteoporosis medications.…”
Section: Health Economicsmentioning
confidence: 99%